Optimasi dan Formulasi Tablet Mengapung - Mucoadhesive Glimepirid dengan Kombinasi Polimer Karbopol dan HPMC K4M (Optimization and Formulation Floating - Mucoadhesive Glimepiride Tablet with Combination Carbopol and HPMC K4M) - Hery Diar Febryanto; Lusia Oktora Ruma Kumala Sari; Eka Deddy Irawan (Pustaka Kesehatan, 2014)
Glimepiride is one of the preferred drug for the treatment of type II diabetes mellitus. Diabetes can affect gastric emptying time. Incomplete absorption of drugs often result in small bioavailability. Glimepiride was chosen as model drug because it has incomplete absorbtion due to less gastric residence time. Tablet make by direct compression using polymer carbopol, HPMC K4M and other additives. This study used factorial design. Factors that are optimazed are carbopol and HPMC K4M and responses used are floating lag time, floating duration time, mucoadhesive, dan DE 720. tablet were evaluated for invitro release characteristic for 12 hours. Area optimum obtained on the composition of the combination of Carbopol 69.20 to 70.60 mg and HPMC K4M 10.66 to 24.67 mg.   Keywords: glimepiride, floating mucoadhesive tablet, release kinetics, carbopol, HPMC K4M